2003
DOI: 10.1136/fn.88.1.f62
|View full text |Cite
|
Sign up to set email alerts
|

An inadequate glycaemic response to glucagon is linked to insulin resistance in preterm infants?

Abstract: Some preterm infants show an inadequate glycaemic response to glucagon and have features suggestive of insulin resistance. The potential long term implications of such insulin resistance may have appreciable public health consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…These data are in accordance with previous studies showing abnormalities in glucose homeostasis in preterm infants in both neonatal and early infant period [36,37]. Later in life, children and adults born preterm display reduced insulin sensitivity and increased insulin secretion [8,18].…”
Section: Discussionsupporting
confidence: 82%
“…These data are in accordance with previous studies showing abnormalities in glucose homeostasis in preterm infants in both neonatal and early infant period [36,37]. Later in life, children and adults born preterm display reduced insulin sensitivity and increased insulin secretion [8,18].…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, the QUICKI has been validated against homeostatic model assessment 52 and has been used in neonates before. 53 Measurement of the QUICKI was carried out at term age and samples taken at the time of routine (pre-feed) blood tests.…”
Section: Quantitative Insulin Sensitivity Check Indexmentioning
confidence: 99%
“…Several studies have reported that many neonates produce an inadequate glucose raising response to decreases in glucose infusion [58] and to a bolus of glucagon [73]. Additionally, it has been shown that many preterm infants have concentrations of hepatic glucose-6-phosphatase, the rate limiting enzyme in gluconeogenesis, below the limit of normal term infants [74].…”
Section: Discussionmentioning
confidence: 99%